2004
DOI: 10.1108/13639510410553121
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐domain work‐family, family‐work conflict and police work satisfaction

Abstract: This research investigates the relationship between inter-domain conflict in the form of work-family conflict and family-work conflict with various facets of employee job satisfaction. The study was conducted among police personnel (n ¼ 119) in a large southeastern state. Results indicate that work-family conflict is significantly related to satisfaction with job in general, pay, supervision, promotion, work, and co-workers. Family-work conflict is not as consistently related to the facets of job satisfaction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
1
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(116 citation statements)
references
References 41 publications
4
98
1
5
Order By: Relevance
“…The current research established that the respondents with higher level of job satisfaction experienced lower level of W-FC. The findings are in consistency with finding of past studies by Namasivayam and Mount (2004), Michael et al (2004), Martins et al (2002), Howard et al (2004), Boles et al (2001), Karimi (2008), Ngah et al (2009) and Cohen and Liani (2009) which have successfully recognized that when work roles interfere with family roles, the individual's job satisfaction is lower. Considering the available evidence, it appears that job satisfaction as work factor, has consistently been shown to be the most significant antecedent of conflict in family domain.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The current research established that the respondents with higher level of job satisfaction experienced lower level of W-FC. The findings are in consistency with finding of past studies by Namasivayam and Mount (2004), Michael et al (2004), Martins et al (2002), Howard et al (2004), Boles et al (2001), Karimi (2008), Ngah et al (2009) and Cohen and Liani (2009) which have successfully recognized that when work roles interfere with family roles, the individual's job satisfaction is lower. Considering the available evidence, it appears that job satisfaction as work factor, has consistently been shown to be the most significant antecedent of conflict in family domain.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the research study by Aryee et al (1999) demonstrated that family-work conflict was negatively related to job satisfaction among Chinese employed parents in dual-earner families. Another study by Howard et al (2004) investigates the relationship between W-FC with employee job satisfaction among police officers in a large south-eastern state in the USA. Results indicate that, when an employee is experiencing conflict between work and family, satisfaction with the job in general and the actual work itself suffer the greatest declines.…”
Section: Job Satisfaction and W-fc And F-wcmentioning
confidence: 99%
“…and talking about problems with the spouse, relative or friend (He et al 2002, Howard et al 2004). For constructing the index, we had to recode the question about reliability on the family ( " I feel that I can rely on support from my family, friends etc.…”
Section: Explanatory and Control Variablesmentioning
confidence: 99%
“…Previous research has shown that work-family conflict leads to various negative outcomes, including job dissatisfaction [6][7][8][9][10] . Thus, taking into account the reality of working life today and the stress-producing nature of work-family conflict, we are forced to reconsider the resources that might help either alleviate work-family conflict or, increase the level of job satisfaction.…”
Section: Introductionmentioning
confidence: 99%